What characterizes the sponsors of the Norwegian Ski Federation cross-country´s incentives towards entering a sponsor relationship? - Olsen, L. K. B. (Molde University College, 2018)
Sponsorships has had an increase of development the last decades, and now commercialization of sports has taken sponsorships in a new direction where economic benefit is more important than ever. In addition to economic benefits sponsors has a lot of other expectations when it comes to sponsor relationships such as exposure, image transfer, brand awareness, motivating employees and increase of sales and market share. Cross-country skiing is the most popular sport in Norway (SponsorInsight 2018), which makes sponsorships in the Norwegian Ski Federation interesting to investigate. Even though the sport has had some recent incidents with unintentional doping the sponsors are still present, which can indicate that there are valuable aspects of the sponsorship that the sponsors cannot afford to lose. The purpose of this thesis is to identify the sponsors of The Norwegian Ski Federation Cross-Country´s (NSFCC) incentives towards the sponsor relationship with the Norwegian Ski Federation. Implicit this includes understanding what characterizes sponsors mind-set related to their objectives when entering a sponsor relationship. That is the background for the research question: What characterizes the Sponsors of the Norwegian Ski Federation Cross-Country´s Incentives Towards Entering a Sponsor Relationship? The empirical part of the thesis is based on five in-depth interviews conducted with the sponsors of the Norwegian Ski Federation Cross-Country. The respondents are responsible for sponsorship agreements in their organization and for the agreement with the Norwegian Ski Federation Cross-Country. The research findings indicate that the sponsors are unanimous in their response when they say the most important factor for entering a sponsorship is congruence between the sponsor and the sponsor object additional to similar values. The sponsors further identify different market-centered objectives that are important for them in order to reach their organizational goals. At last the findings indicate that the sponsors are influenced by a commercial logic which generates that their incentives are based on a mind-set that seeks to achieve economic value.